THE EFFECT OF ORAL CONTRACEPTIVES USE ON DEVELOPMENT OF MENTAL DISORDERS SUCH AS DEPRESSION – A REVIEW ARTICLE - Małgorzata Krzyżanowska,; Natalia Pacocha,; Jakub Jędrychowski,; Justyna Popczyńska,; Natalia Karpowicz,; Marta Zgierska,; Julia Kaszucka,; Agnieszka Raczyńska,; Kinga Kosiec,; Oliwia Krzemień, (International Journal of Innovative Technologies in Social Science, 2024)
IntroductionOral hormonal contraception is considered to be one of the most effective methods used to prevent unwanted pregnancy. The ease of use and wide availability make woman reach for it even more willingly. However, the treatment is associated with a number of adverse effects. The oral contraceptive pills not only interfere with the physical well-being, but also markedly affect mental health and may predispose to the development of mood disorders. The aim of this study is to conduct a comprehensive review of the effect of oral contraceptives use on development of mental disorders, in particular depression.Materials and MethodsA comprehensive review of literature available in the PubMed database was performed. This process involved a thorough search of articles written in English containing the following key terms: “hormonal contraception”, “oral contraceptives”, “oestrogen”, “progesterone”, “mood disorders”, “depression”. The gathered data was then scrupulously examined and analyzed.ResultsStudies show that the use of hormonal contraception is associated with a higher risk of subsequent use of antidepressants and diagnosis of depression. This correlation is particularly prominent in adolescents. Trends show that women taking OCPs with a higher amount of progesterone compound were more likely to develop symptoms of depression.ConclusionsThe evidence suggests a deep correlation between the use of an oral hormonal contraception with the risk of developing mood disorders, such as depression. Further research must be performed in order to determine why some women are more susceptible to such changes of an emotional state during hormone contraceptive treatment, while other present resistance to it.